2008
DOI: 10.1242/jeb.012674
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative defence alterations in skeletal muscle during prolonged acclimation to cold: role ofl-arginine/NO-producing pathway

Abstract: SUMMARYEarly in cold acclimation (1-7·days), heat is produced by shivering, while late in cold acclimation (12-45·days), skeletal muscle contributes to thermogenesis by tissue metabolism other than contractions. Given that both thermogenic phases augment skeletal muscle aerobic power and reactive species production, we aimed in this study to examine possible changes in skeletal muscle antioxidative defence (AD) during early and late cold acclimation with special emphasis on the influence of the Larginine/nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 63 publications
6
29
1
Order By: Relevance
“…In addition, our results suggest that an established molecular basis for increased skeletal muscle lipidbased oxidative metabolism was maintained until the end of the examined time period, when shivering decreased and non-shivering thermogenesis took place. These results are in accordance with our previous data, which showed that from day 3 of cold acclimation there was a conspicuous increase in skeletal muscle catalase and glutathione peroxidase activities, enzymes that remove H 2 O 2 when levels increase because of increased β-oxidation (Petrović et al, 2008). Such a shift toward lipid metabolism in skeletal muscle during prolonged cold exposure highlighted the physiological significance of our recently obtained data concerning white adipose tissue structural ) and endocrine (Jankovic et al, 2013) remodeling during cold acclimation.…”
Section: P<0001 Pgc-1α/ppars In Skeletal Muscle In the Coldsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, our results suggest that an established molecular basis for increased skeletal muscle lipidbased oxidative metabolism was maintained until the end of the examined time period, when shivering decreased and non-shivering thermogenesis took place. These results are in accordance with our previous data, which showed that from day 3 of cold acclimation there was a conspicuous increase in skeletal muscle catalase and glutathione peroxidase activities, enzymes that remove H 2 O 2 when levels increase because of increased β-oxidation (Petrović et al, 2008). Such a shift toward lipid metabolism in skeletal muscle during prolonged cold exposure highlighted the physiological significance of our recently obtained data concerning white adipose tissue structural ) and endocrine (Jankovic et al, 2013) remodeling during cold acclimation.…”
Section: P<0001 Pgc-1α/ppars In Skeletal Muscle In the Coldsupporting
confidence: 93%
“…The cold-acclimated group was divided into three subgroups: (1) untreated, (2) L-arginine treated and (3) L-NAME treated. Drugs were administered in drinking water, as 2.25% Larginine HCl or 0.01% L-NAME HCl, as described previously (Saha et al, 1996;Petrović et al, 2005;Petrović et al, 2008). Rats were housed in individual plastic cages with drinking water and food ad libitum.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Journal of Experimental Biology (2014) doi:10.1242/jeb.092700 mice exposed to cold (Petrovic et al, 2008) and that lifelong exposure to cold caused no significant muscle oxidative damage in wild derived rodents (Selman et al, 2008). Note also that it has recently been demonstrated that physical activity can induce the production of irisin by the muscle, and that this hormone stimulates UCP1 expression and a brown-fat-like development of white adipose cells (Boström et al, 2012).…”
Section: Research Articlementioning
confidence: 99%
“…Yet, very limited information is available regarding the effect of arginine on intestinal antioxidant status in fish. In the rat muscle, it has been shown that arginine significantly enhanced the activities of copper/zinc superoxide dismutase (Cu/ZnSOD), catalase (CAT) and glutathione peroxidase (GPx) [19]. Moreover, the activities of antioxidant enzymes may be associated with their gene transcription levels, which could be regulated by NF-E2-related nuclear factor 2 (Nrf2) and Kelch-like-ECH-associated protein 1 (Keap1) signalling molecules in fish [20].…”
Section: Introductionmentioning
confidence: 99%